Meninjau Perlunya Revisi Regulasi Tindak Pidana Ringan selama Pandemi dalam Hukum Kesehatan - Hotmaria Hertawaty Sijabat (CV. ADIBA AISHA AMIRA, 2024)
The COVID-19 pandemic has brought significant changes in various aspects of life, including in the legal and health sectors. One of the issues of concern is related to minor criminal offences in the health sector, such as drug counterfeiting, smuggling of medical devices, and violation of health protocols. These problems require more comprehensive handling through revision of existing regulations. The method used is a literature study by analysing various related literature sources. The results showed that regulatory revision is very important to do, given the complexity of the problem, law enforcement challenges, and the need to strengthen a more adaptive and effective legal framework. The concept of regulatory revision that needs to be considered includes strengthening the authority of law enforcers, improving coordination, clarifying the typology of criminal offences, toughening sanctions, and encouraging community participation. A more nuanced and proportional approach must also be applied, so that law enforcement does not overburden the community in the midst of a pandemic crisis situation. Regulatory revisions are expected to strengthen public protection, increase compliance, and prevent potential violations in the health sector.